Monetary policy and the illusionary exchange rate puzzle - Hilde C. Bjørnland (University of Oslo, Department of Economics, 2005)
Dornbusch's exchange rate overshooting hypothesis is a central building block in international macroeconomics. Yet, empirical studies of monetary policy have typically found exchange rate effects that are inconsistent with overshooting. This puzzling result has developed into a “styled facts” to be reckoned with in policy modelling. However, many of these studies, in particular those using VARs, have disregarded the strong contemporaneous interaction between monetary policy and exchange rate movements by placing zero restriction on them. By instead imposing a long-run neutrality restriction on the real exchange, thereby allowing the interest rate and the exchange rate to react simultaneously to any news, I find that the puzzles disappear. In particular, a contractionary monetary policy shock has a strong effect on the exchange rate that appreciates on impact. The maximum effect occurs immediately, and the exchange rate thereafter gradually depreciates to baseline, consistent with the Dornbusch overshooting hypothesis and with few exceptions consistent with UIP.
Keywords: C32; E52; F31; F41; 330; Dornbusch overshooting; VAR; monetary policy; exchange rate puzzle; identification; Geldpolitik; Wechselkurs; Overshooting; Theorie; Risikomaß